2019
DOI: 10.3928/23258160-20190905-05
|View full text |Cite
|
Sign up to set email alerts
|

Textural Properties of Choriocapillaris on OCTA in Healed Inflammatory Choriocapillaropathies

Abstract: BACKGROUND AND OBJECTIVE: To evaluate the flow characteristics and textural properties of choriocapillaris (CC) on optical coherence tomography angiography in eyes with resolved inflammatory choriocapillaropathies and Vogt-Koyanagi-Harada (VKH) disease. PATIENTS AND METHODS: A cohort of eyes with healed acute posterior multifocal placoid pigment epitheliopathy (APMPPE), serpiginous choroiditis (SC), and VKH disease were included. A 3 mm × 3 mm OCT angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…In our study, VKH disease patients demonstrated increased CC-FV and FV average size during the acute phase but not the convalescent phase, consistent with previous studies reporting that systemic corticosteroids can mitigate FV ( 17 , 22 , 24 , 40 ). Indeed, the CC-FV observed in convalescent-stage VKH disease patients did not differ significantly from those measured in HCs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, VKH disease patients demonstrated increased CC-FV and FV average size during the acute phase but not the convalescent phase, consistent with previous studies reporting that systemic corticosteroids can mitigate FV ( 17 , 22 , 24 , 40 ). Indeed, the CC-FV observed in convalescent-stage VKH disease patients did not differ significantly from those measured in HCs.…”
Section: Discussionsupporting
confidence: 92%
“…Further, the CC-FV area fraction and CC-VPD correlated strongly with logMAR BCVA during the convalescent phase. The CC-VPD was also dramatically reduced during the acute stage but fully restored during the convalescent phase, in contrast to several previous reports (21)(22)(23)44). We speculate that this reflects effective recovery of CC blood flow after appropriate treatment.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…It has been found that CC plays a major role in different retinal pathologies such as age-related macular degeneration, 4,5 systemic hypertension,6 myopic maculopathy, 7 macular telangiectasia type 2, 8 retinal dystrophies, 9 or inflammatory choriocapillaropathies. 10 Choroidal vascularization remains difficult to measure due to light scattering when passing through the overlaying tissues and the retinal pigmentary epithelium (RPE). However, vascular density (VD), flow void areas and the choroidal vascular index (CVI) have been used.…”
Section: Introductionmentioning
confidence: 99%